The Schumpeterian entrepreneur: a review of the empirical evidence on the antecedents, behaviour and consequences of innovative entrepreneurship. Issue 1 (24th November 2016) - Block, Joern H.; Fisch, Christian O.; van Praag, Mirjam
Abstract: Innovative entrepreneurship is considered an important pillar for economic development and has sparked a lively discussion in academia and practice alike. Oftentimes, however, the debate is not sufficiently grounded on solid empirical evidence. The academic literature is growing but very scattered and is separated into several disciplines. We provide a summary that takes stock of the academic knowledge about innovative entrepreneurship and summarizes the evidence from 102 empirical studies published in the primary economics and management journals on the antecedents, behavior, and consequences of innovative entrepreneurship. Based on this state-of-the-art literature review, directions for future research are discussed.